PENINGKATAN HASIL BELAJAR MATERI INDONESIAKU KAYA BUDAYA MENGGUNAKAN MEDIA FLASH CARD SIS - Emilia Diah Pratama; Fida Rahmantika Hadi; Titik Isdarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to improve the learning outcomes of Indonesiaku Kaya Budaya material by using flash card media for class IV students at SDN 01 Taman Madiun. The research method used is classroom action research through two cycles. The first cycle aims to evaluate student learning outcomes before using flash card media, while the second cycle aims to see an increase in learning outcomes after implementing flash card media. The results of the first cycle of research show that the use of flash card media has provided an increase in student learning outcomes. Achievement of test indicators, student activity and cooperation increased significantly compared to previous conditions. Even though the overall indicator target has not been achieved, there has been a positive increase in students' understanding of the material Indonesiaku Kaya Budaya. Furthermore, the results of cycle II research showed a more significant increase in student learning outcomes after implementing flash card media. Achievement of test indicators, student activity and cooperation exceeds the specified indicator targets. This shows that the use of flash cards as a learning medium is effective in increasing students' understanding of the material Indonesiaku Kaya Budaya. In conclusion, the use of flash card media has succeeded in improving the learning outcomes of class IV students at SDN 01 Taman Madiun in understanding the material Indonesiaku Kaya Budaya. Teachers and parties involved in education need to support the use of flash card media in learning and ensure the availability of the necessary resources. It is hoped that this research can contribute to the development of innovative and effective learning strategies and increase students' understanding of their cultural richness.